LZCOMPLEXITY: BIBLIOTECA PARA EL CÁLCULO DE MEDIDAS ENTRÓPICAS. - ARAGÓN-PÉREZ, E.; ESTÉVEZ-RAMS, E. (Revista Cubana de Física, 2025)
The library Izcomplexity is presented, developed for complexity analysis using entropic metrics. The algorithms used to estimate the metrics by means of Lempel-Ziv factorization are described. To face the computational challenges associated with the analysis of large volumes of data, Izcomplexity implements algorithms that enable parallel processing of the sequences. The experiments carried out and its practical use demonstrate that Izcomplexity can analyze long sequences in reasonable times and that the included entropic measures are reliable indicators for describing complex systems.